2014
DOI: 10.1371/journal.pone.0092979
|View full text |Cite
|
Sign up to set email alerts
|

Where, When and What? A Time Study of Surgeons' Work in Urology

Abstract: IntroductionStaff time is a relevant resource in the delivery of health care interventions. Its measurement is a prerequisite for unit costing but usually complex. The aim of this study was to analyse the distribution of surgeons' work time among types and places of activities. A second aim was to use these data to calculate costs per unit of output.MethodsA self-reporting work sampling study was carried out at a department of Urology. All of twelve surgeons involved in clinical care participated in a two-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Understanding differences in resource use between groups of patients is vital for the efficient organisation of health care [ 1 ]. Respective data are required by health care providers for managerial decision-making, such as determining appropriate staffing levels and controlling of budgets [ 2 , 3 ]. Moreover, they inform policy makers considered with the efficient allocation of funds on a system level, for instance by the design of reimbursement schemes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding differences in resource use between groups of patients is vital for the efficient organisation of health care [ 1 ]. Respective data are required by health care providers for managerial decision-making, such as determining appropriate staffing levels and controlling of budgets [ 2 , 3 ]. Moreover, they inform policy makers considered with the efficient allocation of funds on a system level, for instance by the design of reimbursement schemes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Travel time to clients' homes, where doula visits often take place, was not included in this analysis, but doulas' travel time is important to consider. 19 Most time-use studies in healthcare use self-reported data 35,51 or observation [36][37][38]41 to track the time spent by providers on different activities; others approach time use from a per client perspective by tracking all activities related to a client over a specific period of time. 52,53 We did not include any observational methods, so all data are based on doulas' self-reports and potentially subject to self-report and social desirability biases.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 33 In healthcare settings, time-use studies are commonly used in the context of quality improvement and cost effectiveness. 34 Time-use studies with healthcare providers, 35 38 including community health workers, 39 41 exist, but we are not aware of any similar systematic efforts to track doulas’ time use.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, work-sampling uses snap-shots of subject’s activities, usually at random points of time, in order to estimate total work time distribution [ 15 ]. Work-sampling was found to produce results of similar validity in comparison to time-and-motion studies [ 16 ] and its efficient design allows incorporating large numbers of staff [ 17 ].…”
Section: Introductionmentioning
confidence: 99%